2021
DOI: 10.12669/pjms.38.1.3992
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and Compliance of surviving sepsis campaign: A retrospective cohort study at tertiary care hospital

Abstract: Background and Objective: Sepsis is one of the leading causes of direct maternal mortality in Pakistan. It is recommended that the first three hours after the presentation are crucial. During this time implementation of surviving sepsis campaign resuscitation bundles reduces maternal mortality. Our objective was to assess the factors contributing to puerperal sepsis and the compliance of “surviving sepsis campaign resuscitation bundles in puerperal sepsis” for the management of puerperal sepsis. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Data from China demonstrated that in 2022 alone, a total of 25.5% of intensive care unit (ICU) patients were diagnosed with sepsis and in ~13% of these cases sepsis progressed to septic shock that is associated with severe circulatory, cellular, coagulation and metabolic abnormalities that lead to higher risk of mortality compared with uncomplicated sepsis (4). Diagnosis of sepsis is difficult due to the lack of signs and symptoms and absence of any gold standard test (1,2). It is considered a major public health concern, with high morbidity and mortality, and a heavy economic burden on the healthcare system (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from China demonstrated that in 2022 alone, a total of 25.5% of intensive care unit (ICU) patients were diagnosed with sepsis and in ~13% of these cases sepsis progressed to septic shock that is associated with severe circulatory, cellular, coagulation and metabolic abnormalities that lead to higher risk of mortality compared with uncomplicated sepsis (4). Diagnosis of sepsis is difficult due to the lack of signs and symptoms and absence of any gold standard test (1,2). It is considered a major public health concern, with high morbidity and mortality, and a heavy economic burden on the healthcare system (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Sepsis is a complex syndrome caused by pathophysiological and biochemical dysregulation triggered by autogenous factors in response to bacterial, viral, parasitic or fungal infections ( 1 , 2 ). According to the 1997-2017 Global Burden of Disease Study, there were 48.9 million sepsis cases and ~11 million sepsis-related deaths in the past two decades ( 3 ).…”
Section: Introductionmentioning
confidence: 99%